Materials for Sustainable Infrastructure Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume includes a unique group of chapters focusing on new advances in materials for infrastructure sustainability. Chapters have been well-organized and handled by a group of international experts in order to discuss a timely topic with regards to the sustainable infrastructures. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.